2021
DOI: 10.1007/s11665-021-05562-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multiwalled Carbon Nanotubes on Improvement of Fracture Toughness of Spark-Plasma-Sintered Yttria-Stabilized Zirconia Nanocomposites

Abstract: Highly dense yttria-stabilized zirconia (YSZ) nano-ceramics reinforced with TC-CVD-synthesized multiwall carbon nanotubes (MWCNTs) were fabricated using spark plasma sintering at a temperature of 1350°C, the heating rate of 100 °C/min and pressure of 50MPa with a dwell time of 10 minutes. The identical parameters were utilized for fabricating composites with a varying weight ratio of YSZ and MWNCTs. The samples were characterized for their phase transformation, microstructure and elemental composition using x-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 57 publications
3
24
0
Order By: Relevance
“…Although in many applications the use of micro sized reinforcements has failed to provide the required strength. So, researchers have tended towards nanoparticles which need special reinforcing mechanisms such as Orowan mechanism, thermal discrepancy and load transfer mechanisms to strengthen the cermet according to applicational requirements [6][7][8]. Many researchers have worked on the reinforcement of aluminium alloys using single reinforcements such as SiC and TiO 2 [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although in many applications the use of micro sized reinforcements has failed to provide the required strength. So, researchers have tended towards nanoparticles which need special reinforcing mechanisms such as Orowan mechanism, thermal discrepancy and load transfer mechanisms to strengthen the cermet according to applicational requirements [6][7][8]. Many researchers have worked on the reinforcement of aluminium alloys using single reinforcements such as SiC and TiO 2 [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The surface topographies of the samples were obtained using a scanning electron microscope (ZEISS SUPRA 55), and simultaneously quantitative elemental analysis was conducted as per ASTM D4541 [26] , [27] . The density was measured using Archimedes method of liquid displacement using water as a liquid medium, and porosity (%) was calculated from the density [28] . Vickers hardness was measured using a diamond intender at a load of 10 N and a dwell time of 20 sec as per ASTM E92 (Vickers hardness machine, Krystal Elmec, India).…”
Section: Methodsmentioning
confidence: 99%
“…Tensile test (UTM Zwick, Germany) was carried out as per ASTM E8/E8M-11 at a standard displacement of 0.5 mm/min. Wear behaviour of the samples were studied using a pin on disc tester (Ducom TR-20LE-PHM-400) as per ASTM G99 standards at a sliding speed of 2 m/s and varying load (20 N and 40 N) and sliding distance (600 m and 1200 m) [28] , [29] . Thermal expansion (CLTE) was measured (Anter Unitherm Model-1161 V) under argon atmosphere as per ASTM E228, and thermal conductivity (TC) was measured (Netzsch LFA-467) as per ASTM E1225-13.…”
Section: Methodsmentioning
confidence: 99%
“…However, few reports of Arunkumar et al reported that the physical techniques were not able to be satisfactory in providing only through single physical techniques therefore he utilised two or more techniques to support higher homogeneous distribution. The report also specified that with increase in CNTs content, the rate of uniform distribution reduces owing to increase in Vander Waal force of attraction between CNTs particles [31].…”
Section: Sol-gel Routementioning
confidence: 99%
“…Various research has been conducted to enhance the fracture toughness of the ceramics by reinforcing them with various materials including metal and ceramic additives. Although with the potential of CNTs being a suitable reinforcement material, research work on incorporating CNTs has proved to be effective to ceramics composites as studies have demonstrated enhancement in fracture behaviour [31][32][33].…”
Section: Introductionmentioning
confidence: 99%